Anti‐GPVI nanobody blocks collagen‐ and atherosclerotic plaque–induced GPVI clustering, signaling, and thrombus formation. (12th August 2022) - Jooss, Natalie J.; Smith, Christopher W.; Slater, Alexandre; Montague, Samantha J.; Di, Ying; O'Shea, Christopher; Thomas, Mark R.; Henskens, Yvonne M. C.; Heemskerk, Johan W. M.; Watson, Steve P.; Poulter, Natalie S.
Abstract: Background: The collagen receptor glycoprotein VI (GPVI) is an attractive antiplatelet target due to its critical role in thrombosis but minor involvement in hemostasis. Objective: To investigate GPVI receptor involvement in platelet activation by collagen‐I and atherosclerotic plaque using novel blocking and non‐blocking anti‐GPVI nanobodies (Nbs). Methods: Nb effects on GPVI‐mediated signaling and function were assessed by western blot and whole blood thrombus formation under flow. GPVI clustering was visualized in thrombi using fluorescently labeled Nb28. Results: Under arterial shear, inhibitory Nb2 blocks thrombus formation and platelet activation on collagen and plaque, but only reduces adhesion on plaque. In contrast, adhesion on collagen, but not plaque, is decreased by blocking integrin α2β1. Adhesion on plaque is maintained despite inhibition of integrins αvβ3, α5β1, α6β1, and αIIbβ3. Only combined αIIbβ3 and α2β1 blockade inhibits adhesion and thrombus formation to the same extent as Nb2 alone. Nb2 prevents GPVI signaling, with loss of Syk, Lat, and PLCɣ2 phosphorylation, especially to plaque stimulation. Non‐blocking fluorescently labeled Nb28 reveals distinct GPVI distribution patterns on collagen and plaque, with GPVI clustering clearly apparent on collagen fibers and less frequent on plaque. Clustering on collagen fibers is lost in the presence of Nb2. Conclusions: This work emphasizes the critical difference in GPVI‐mediated platelet activation by plaque and collagen; it highlights the importance of GPVI clustering for downstream signaling and thrombus formation. Labeled Nb28 is a novel tool for providing mechanistic insight into this process and the data suggest Nb2 warrants further investigation as a potential anti‐thrombotic agent.